Antidiabetic Test of Breadfunnel Leaves (Artocarpus communis) on Reducing Blood Sugar Levels In Mice (Mus musculus) - Wa Ode Nur Asni; Sarni; Yayuk Sri Rahayu (International Journal of Multidisciplinary Learners, 2025)
Breadfruit tree is one of the traditional medicinal plants that is believed to have antidiabetic activity, where breadfruit leaves contain flavonoids, have good benefits for health when consumed because they have the property of lowering blood sugar levels. This study aims to conduct an antidiabetic test of breadfruit leaves (Artocarpus communis) on reducing blood glucose in mice (Mus muculus). From the phytochemical research that has been done, several compounds of breadfruit leaves were obtained such as riboflavin, tannin, potassium, acetylcholine, hydrocyanic acid and so on. These compounds can treat infections, reduce cholesterol levels and liver disease, inflammation, heart, kidneys, blood vessels. Ethanol extract of breadfruit leaves has shown results that can regulate fasting blood glucose levels and glucose tolerance(Lee et al., 2012). Based on research (Mu'nisa et al., 2012) found that mice given ethanol extract with alloxan induction can reduce blood sugar levels. Breadfruit leaf extract has anti-free radical activity derived from the high antioxidant compounds it contains(Suryanto & Frenly, 2019). Breadfruit leaves can also improve the non-specific immune system in mice.(Yuswantina et al., 2013). The type of research used was a laboratory experiment with a maceration method for in vivo extraction using mice (Mus musculus) as test animals. The treatment group was divided into 3 groups, including a positive control group (glibenclamide suspension), dose group I 500 mg/kg BW, and dose group II 1000 mg/kg BW which was tested for 10 days. Based on the results of this study, that breadfruit leaf extract (Artocarpus communis) has antidiabetic activity. A dose of 1000 mg/kg BW showed a decrease of 38.99%, greater than a dose of 500 mg/kg BW which showed a decrease of 33.58%.